(untitled) (DA NANG JOURNAL OF MEDICINE AND PHARMACY, 2026)
Serotonin syndrome is an acute, potentially life-threatening toxic condition resulting from excessive serotonergic activity in the central nervous system. It most commonly occurs after the use of antidepressants, particularly selective serotonin reuptake inhibitors, serotonin-norepinephrine reuptake inhibitors, or in combination with other serotonergic agents. The typical clinical presentation consists of a triad of altered mental status, neuromuscular hyperactivity, and autonomic dysfunction. In severe cases, the condition may rapidly progress to malignant hyperthermia, rhabdomyolysis, multiorgan failure, and death if not promptly recognized and treated. We report a case of severe serotonin syndrome in a 21-year-old female following sertraline use. The patient developed malignant hyperthermia (peak temperature 41°C), generalized hypertonia, ocular clonus, seizures, and rhabdomyolysis. Management included immediate discontinuation of the offending agent, intensive supportive care, and the implementation of Targeted Temperature Management (TTM) with a core temperature target of 37°C maintained for eight days. The patient demonstrated marked clinical improvement and achieved complete recovery. This case suggests that TTM may be a safe and effective therapeutic option in fulminant serotonin syndrome with refractory hyperthermia.